Increased ascorbic acid content in chronic lymphocytic leukemia B lymphocytes. - Liebes, L (1981)
Human lymphocyte extracts analyzed by high-performance liquid chromatography reveal a major UV-absorbing peak that was shown to be ascorbic acid by spectral, chemical, and enzymatic criteria. Because this peak appeared very prominent in the elution profile of chronic lymphocytic leukemia (CLL) lymphocyte extracts, we measured the ascorbic acid content in lymphocytes from the blood of normal subjects and untreated patients with chronic lymphocytic leukemia. A significantly higher concentration of 111 +/- 15.3 nmol per 10(8) cells (mean +/- SEM) was found in CLL lymphocytes than in normal blood lymphocytes, which contained 42.2 +/- 3.3 nmol per 10(8) cells. Selective enrichment with B and T cells showed that this difference was limited to the chronic lymphocytic leukemia B cell, which had a 5- to 15-fold higher content of ascorbic acid than normal B cells had. In contrast, the ascorbic acid level was similar in normal and CLL T cells. The very high ascorbic acid content provides the chronic lymphocytic leukemia B cell with a reducing substance that could react with oxidants or free radicals.